Interculturalism in Indonesian ELT - Rachmatika, Dian; Izzah, Navisatul (New Language Dimensions, 2024)
The integration of culture in language classrooms is crucial to enhance students’ translingual and transcultural competence. This is particularly relevant in English Language Teaching (ELT), where English serves as a global lingua franca among multicultural users. Effective communication requires both language proficiency and cultural literacy. In Indonesia, where English is taught and learned by individuals from diverse cultural backgrounds, the Ministry of Higher Education mandates the inclusion of cross-cultural subjects in teacher education. However, many English as a Foreign Language (EFL) teachers feel unprepared to integrate cultural elements due to a lack of training and models. This essay explores the challenges of cultural integration in Indonesian teacher education, reviews related literature and case studies, and proposes strategies to enhance cultural inclusion in language teaching.